All Pseudocapacitive MXene‐RuO2 Asymmetric Supercapacitors. Issue 13 (23rd January 2018) - Jiang, Qiu; Kurra, Narendra; Alhabeb, Mohamed; Gogotsi, Yury; Alshareef, Husam N.
Abstract: 2D transition metal carbides and nitrides, known as MXenes, are an emerging class of 2D materials with a wide spectrum of potential applications, in particular in electrochemical energy storage. The hydrophilicity of MXenes combined with their metallic conductivity and surface redox reactions is the key for high‐rate pseudocapacitive energy storage in MXene electrodes. However, symmetric MXene supercapacitors have a limited voltage window of around 0.6 V due to possible oxidation at high anodic potentials. In this study, the fact that titanium carbide MXene (Ti3 C2 T x ) can operate at negative potentials in acidic electrolyte is exploited, to design an all‐pseudocapacitive asymmetric device by combining it with a ruthenium oxide (RuO2 ) positive electrode. This asymmetric device operates at a voltage window of 1.5 V, which is about two times wider than the operating voltage window of symmetric MXene supercapacitors, and is the widest voltage window reported to date for MXene‐based supercapacitors. The complementary working potential windows of MXene and RuO2, along with proton‐induced pseudocapacitance, significantly enhance the device performance. As a result, the asymmetric devices can deliver an energy density of 37 µW h cm −2 at a power density of 40 mW cm −2, with 86% capacitance retention after 20 000 charge–discharge cycles. These results show that pseudocapacitive negative MXene electrodes can potentially replace carbon‐based materials in asymmetric electrochemical capacitors, leading to an increased energy density. Abstract : The complementary working potential windows of MXene and RuO2, along with proton‐induced pseudocapacitance, leads to the design of all‐pseudocapacitive asymmetric devices providing enhanced energy density.